How 10-MDP functional phosphate monomer and 2% digluconate chlorhexidine solution interact on sound, artificial carious or eroded dentin substrates - Jacomine, Juliana Carvalho (2019)
Objective: Carious and eroded dentin represent common modified dental substrates, which mostly require restorative procedures. MDP-based dentin bonding system (DBS) and digluconate chlorhexidine (CHX) are presented as promising agents to minimize intrinsic degradation of the resin-dentin interface by interaction with calcium (Ca). Therefore, the purpose of this study was to explore the possible interaction between MDP in a universal adhesive system with 10-MDP in self-etching mode and CHX on substrates artificially modified by caries and erosion, through microtensile bond strength (TBS). Additional characterization of the adhesive interface was performed by SEM/EDS analyses. Material and methods: Flat dentin surfaces were obtained from 120 specimens (n=20/group) prepared from extracted sound human third molars and randomly divided into three groups according to the dentin substrate: sound-control (S), artificial carious (C) and artificial eroded (E). Half of these specimens were pretreated with distilled water (W) and other half with 2% CHX, constituting 6 groups: SW, S-CHX, C-W, C-CHX, E-W, E-CHX. After, all the specimens were restored with a universal adhesive system (Apder Single Bond Universal) using self-etching mode and two increments of composite resin (Filtek Z-350), following manufacturers instructions. Slices (0.8mm) were obtained to SEM analysis and beams (0.64mm²) were obtained and evaluated by EDS analysis and TBS in universal testing machine (500N/ 0.5mm/min) after 24 hours and 6 months. Data was statistically analyzed by two-way ANOVA and Tukey tests (p<0.05). Results: Substrate type was a statistically significant factor (p<0.0001), whereas the pretreatment (p=0.189), time (p=0.337) and the interaction between three factors (p=0.452) were not significant. Conclusion: Carious and eroded dentin substrates negatively interfered on the bond strength of an MDP- based universal adhesive systems, regardless its use with CHX. Likely, the reduction of available calcium from these substrates impaired the effectiveness of this system.